Severe Meesmann's epithelial corneal dystrophy phenotype due to a missense mutation in the helix-initiation motif of keratin 12 - Hassan, H (Nature Publishing Group, 2013)
PURPOSE: To describe a severe phenotype of Meesmann's epithelial corneal dystrophy (MECD) and to determine the underlying molecular cause. METHODS: We identified a 30-member family affected by MECD and examined 11 of the 14 affected individuals. Excised corneal tissue from one affected individual was examined histologically. We used PCR and direct sequencing to identify mutation of the coding regions of the KRT3 and KRT12 genes. RESULTS: Cases had an unusually severe phenotype with large numbers of intraepithelial cysts present from infancy and they developed subepithelial fibrosis in the second to third decade. In some individuals, the cornea became superficially vascularized, a change accompanied by the loss of clinically obvious epithelial cysts. Visual loss from amblyopia or corneal opacity was common and four individuals were visually impaired (≤6/24 bilaterally) and one was blind (<6/60 bilaterally). In all affected family members, there was a heterozygous missense mutation c. 395T>C (p. L132P) in exon 1 of the KRT12 gene, which codes for the helix-initiation motif of the K12 polypeptide. This sequence change was not found in unaffected family members or in 100 unaffected controls. CONCLUSIONS: The Leu132Pro missense mutation is within the helix-initiation motif of the keratin and is predicted to result in a significant structural change of the K12 protein. The clinical effects are markedly more severe than the phenotype usually associated with the Arg135Thr mutation within this motif, most frequently seen in European patients with MECD.